Simulations of the spread of COVID-19 and control policies in Tunisia - Slimane Ben Miled; Amira Kebir (AOSIS, 2021)
Background: On March 11, 2020, the WHO announced that the COVID-19 outbreak had become pandemic, indicating that it was au- tonomous on several continents. Tunisia's targeted containment and screen- ing strategy aligns with the WHO's initial guidelines. This method is now showing its limitations. Mass screening in some countries shows that asymptomatic patients play an important role in spreading the virus through the population. Objective: Our goals are first to assess Tunisia's COVID-19 control policies, and then understand the effect of various detection, quarantine and confinement strategies and the rule of asymptomatic patients on the spread of the virus in the Tunisian population. Methods: We develop and analyze a mathematical and epidemiologi- cal models for COVID- 19 in Tunisia. The data come from the Tunisian Health Commission dataset. Results: We calibrate different parameters of the model based on the Tunisian data, we calculate the expression of the basic reproduction num- ber R0 as a function of the model parameters and, finally, we carry out simulations of interventions and compare different strategies for suppress- ing and controlling the epidemic. Conclusions: We show that Tunisia's control policies are effective in screening infected and asymptomatic persons.